Analisis Strategi Kompensasi yang Efektif untuk Meningkatkan Motivasi dan Kinerja Karyawan di PT Hutahaean - Richand Oktovia Br Sihombing; Mariana Simanjuntak (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research explores the urgency of developing effective compensation strategies as a key factor in increasing employee motivation and performance at PT Hutahaean. Fair and adequate compensation is considered an incentive for employees to make maximum contributions and remain loyal to the company, especially in an increasingly competitive labor market. This research aims to formulate a compensation program design that provides significant incentives and analyze its impact on employee satisfaction levels. A qualitative literature study method was used to detail important findings, including the dominance of financial compensation variables on performance. The findings emphasize the crucial role of a fair and transparent compensation system, and recommendations include regular system updates, increased attention to non-financial compensation, and implementation of compensation fairness. Thus, this research provides concrete and relevant views for PT Hutahaean in improving its compensation strategy.